2022
DOI: 10.1088/1748-0221/17/01/c01003
|View full text |Cite
|
Sign up to set email alerts
|

Stray radiation produced in FLASH electron beams characterized by the MiniPIX Timepix3 Flex detector

Abstract: This work aims to characterize ultra-high dose rate pulses (UHDpulse) electron beams using the hybrid semiconductor pixel detector. The Timepix3 (TPX3) ASIC chip was used to measure the composition, spatial, time, and spectral characteristics of the secondary radiation fields from pulsed 15–23 MeV electron beams. The challenge is to develop a single compact detector that could extract spectrometric and dosimetric information on such high flux short-pulsed fields. For secondary beam measurements, PMMA plates of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The newly developed semiconductor pixel detector demonstrated a robust response under UHDR conditions from individual detector elements. Challenges still exist in managing a large data set with a high acquiring rate sampled with thousands of detectors 42 . Scintillation‐based detectors usually provide high spatiotemporal resolution for the spot size and position measurement 43–45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly developed semiconductor pixel detector demonstrated a robust response under UHDR conditions from individual detector elements. Challenges still exist in managing a large data set with a high acquiring rate sampled with thousands of detectors 42 . Scintillation‐based detectors usually provide high spatiotemporal resolution for the spot size and position measurement 43–45 .…”
Section: Discussionmentioning
confidence: 99%
“…31,34,[43][44][45] 2D pixel detector array is widely used for patient-specific QA measurements, but saturation to UHDR invalidated most commercial detector arrays for FLASH-RT Challenges still exist in managing a large data set with a high acquiring rate sampled with thousands of detectors. 42 Scintillation-based detectors usually provide high spatiotemporal resolution for the spot size and position measurement. [43][44][45] A recent study reported great results on a new scintillation detector with a fast, intensified CMOS camera for PBS dose rate measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The readout chip contains a matrix of 256 × 256 pixels (total 65 536 independent channels, pixel size 55 µm) and an active sensor area of 14 mm × 14 mm for a total sensitive area of 1.98 cm 2 [6]. This detector has the readout electronics detached from the Timepix3 ASIC and a sensor assembly to minimize scattering and self-shielding by using a 5-cm-long flexible printed circuit board [7]. Thanks to the timestamp of each hit with the precision of 1.5 ns and the energy absorbed in each individual pixel, the pixelized structure of the sensor allows recording of particle tracks.…”
Section: Timepix3 Pixel Detectormentioning
confidence: 99%
“…In that aim, customised detectors, based on the Timepix3 chip, were equipped with thermal neutron converters made out of a 6 LiF compound (Šolc et al 2022) to allow for measurements of thermal neutron flux in real time. To achieve the goal of this investigation, an enhanced method for particle field characterization with emphasis on thermal neutron imaging and detection using the highly-integrated miniaturized MiniPIX Timepix3 module in miniaturized customised architecture (Oancea et al 2022 was developed. In this investigation, a calibration of individual converters was performed in a reference field and the corresponding thermal neutron detection efficiency was determined.…”
Section: Introduction and Goalsmentioning
confidence: 99%